Tongue Postures and Tongue Centers: A Study of Acoustic-Articulatory Correspondences Across Different Head Angles - Chiu, Chenhao; Weng, Yining; Chen, Bo-wei (Frontiers in Psychology, 2022)
Recent research on body and head positions has shown that postural changes may induce varying degrees of changes on acoustic speech signals and articulatory gestures. While the preservation of formant profiles across different postures is suitably accounted for by the two-tube model and perturbation theory, it remains unclear whether it is resulted from the accommodation of tongue postures. Specifically, whether the tongue accommodates the changes in head angle to maintain the target acoustics is yet to be determined. The present study examines vowel acoustics and their correspondence with the articulatory maneuvers of the tongue, including both tongue postures and movements of the tongue center, across different head angles. The results show that vowel acoustics, including pitch and formants, are largely unaffected by upward or downward tilting of the head. These preserved acoustics may be attributed to the lingual gestures that compensate for the effects of gravity. Our results also reveal that the tongue postures in response to head movements appear to be vowel-dependent, and the tongue center may serve as an underlying drive that covariates with the head angle changes. These results imply a close relationship between vowel acoustics and tongue postures as well as a target-oriented strategy for different head angles.